L’Androgyne et le Faune: Travesty from Gisèle d’Estoc to Guy de Maupassant (Itinera, 2016)
Following the revisionism of the 1970s, correspondence and journalistic contributions by Guy de Maupassant have been re-evaluated, widening our perspective on the writer’s ambiguous sexual life and his conflicted relationship with women. In between his correspondences, the character of Gisèle d’Estoc emerges as particularly interesting given her triple nature as adulterous, bisexual and crossdresser. The woman’s masquerade relates with the author’s own imagery and literary disguise, expressed through the mythological figure of the faun, which hides and exhibits at once his dichotomous relationship with the modern world.